2018
DOI: 10.1590/1984-70332018v18n3a38
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of harvest index in common bean

Abstract: The aim of this study was to verify if the harvest index (HI) of common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Indeed, this was observed in the F2:4 generation through the extensive occurrence of angular leaf spot and especially bacterial blight, favored by higher temperature and relative humidity. These results are frequently observed in other studies conducted in the region (Arantes et al, 2010;Pinto Júnior et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, this was observed in the F2:4 generation through the extensive occurrence of angular leaf spot and especially bacterial blight, favored by higher temperature and relative humidity. These results are frequently observed in other studies conducted in the region (Arantes et al, 2010;Pinto Júnior et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, this results revealed that the highest and the lowest harvest index were observed in the clones derived from the same parental genotypes, i.e., Kidal (KDL) and NPL-01 but the direction of the cross dictated their harvest index performance, indicating that maternal effect probably influences the harvest index of these F 1 reciprocal hybrids. Since harvest index is a function of two complex traits (Bhagsari and Ashley 1990;Júnior et al 2018), i.e., the dry matter contents of the biological (vegetative) yield and yield; thus, it is hard to explain the existence of maternal effect in this case without having detailed genetic information on these two complex traits. Harvest index in sweet potato had been reported to be positively correlated with root dry matter content (Bhagsari and Ashley 1990) but Mbusa et al (2018) reported no correlation between the two variables.…”
Section: Yield Component and Yield Variablesmentioning
confidence: 99%
“…In general, the genotypes that are more tolerant to abiotic stresses have a higher HI value, that is, a greater ability to partition photo-assimilates from vegetative organs to seeds (Assefa et al, 2015). In common bean, HI values have varied between 0.3 and 0.6, being considered a complex trait and strongly influenced by environment (Pinto Juńior et al, 2018). According to Beebe et al (2008), the increase in HI is a key strategy in the improvement of beans, mainly under abiotic stress conditions.…”
Section: Interaction Between Factors and Influence Of Nitrogen Fertilmentioning
confidence: 99%